2019
DOI: 10.1186/s12884-018-2155-9
|View full text |Cite
|
Sign up to set email alerts
|

Client-tailored maternity care to increase maternal empowerment: cluster randomized controlled trial protocol; the healthy pregnancy 4 All-2 program

Abstract: BackgroundThe postpartum period is an important period for preventive strategies as common maternal and child health risks may become manifest. Women with a lower socioeconomic status tend to have lower maternal empowerment. Increasing their risks of adverse maternal and child health outcomes. This study aims to assess the effectiveness of a primary care level intervention. Delivered to maternity care assistants, aiming to increase maternal empowerment postpartum.MethodsThis study is part of the Dutch nationwi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…On the other hand, an increase in adiponectin in both MP and UCP in Enterotype II group was observed. Daryasari et al observed differences on maternal plasma adiponectin levels depending on the mode of delivery [ 43 ]. They found that umbilical cord blood from vaginal delivery had higher levels of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, an increase in adiponectin in both MP and UCP in Enterotype II group was observed. Daryasari et al observed differences on maternal plasma adiponectin levels depending on the mode of delivery [ 43 ]. They found that umbilical cord blood from vaginal delivery had higher levels of adiponectin.…”
Section: Discussionmentioning
confidence: 99%
“…Lack of friendly maternal health services have previously been cited as a major barrier to adoption of maternal healthcare seeking behavior in low resource settings [31]. Providing tailored information could potentially increase women's knowledge, understanding, and engagement while at the same time creating a sense of empowerment to cope with pregnancy, which can prevent adverse maternal and child health outcomes [32]. Since they can be watched, paused, and repeated anytime, the videos and audios provide an opportunity for self-paced learning which facilitates learning and recall, that may otherwise not be possible with face-to-face approaches.…”
Section: Discussionmentioning
confidence: 99%
“…We conducted a cluster-randomised controlled trial (C-RCT) in six municipalities in the Netherlands to assess the effectiveness of a complex intervention to advance maternal empowerment in the postpartum period [ 24 , 25 ]. The intervention consisted of a systematic risk assessment including both medical and social factors, and a patient-centred, risk-guided approach to address risks identified during pregnancy and the postpartum period.…”
Section: Methodsmentioning
confidence: 99%
“…The study design and rationale are briefly outlined below; a detailed study protocol was previously published ( S1 File ) [ 25 ]. This two-arm, parallel, pragmatic C-RCT was conducted with 12 independent maternity care organisations, which were geographically spread over the Netherlands with 16 offices ( Fig 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation